Geographic Information System of Recording and Analyzing Geographic Data on Traffic Control Facilities - Poletaikin, Alexei N.; Monastyrskaya, Tatiana I.; Skvortsova, Elena B.; Englezi, Irina P. (2024 IEEE 3rd International Conference on Problems of Informatics, Electronics and Radio Engineering (PIERE), 2024)
The research is related to the development of interactive applications for processing geodata about the state of the road network in cities. This area is rapidly developing and is promising for research, analysis and development of information systems. Due to a number of shortcomings of the existing geographic information systems the goal was set to develop a new advanced geographic information system considering the problems described above. To achieve this goal, it was necessary to develop new mathematical models for analyzing geodata on the state of technical means of traffic management. Also, the solutions about maintenance of these means had to be developed. An analysis of the subject area was carried out, on the basis of which the task of creating a geographic information system was set. Using modern tools, a geographic information system prototype was developed and its user testing was carried out. Research has shown the best results when developing an optimal solution using the method of genetic algorithms.